BAGAIMANA EFEKTIVITAS PENGELOLAAN DANA DESA UNTUK PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KESEJAHTERAAN? (Studi pada Desa Trutup Kecamatan Plumpang Kabupaten Tuban) - Tyas Rahayu Kartika; Ratna Rahayu Nengseh; Fitriyah Dwi Febriana (JURNAL EKOMBIS, 2020)
Trutup Village is one of the villages in Tuban Regency that receives funding from the central government in the form of village funds. The purpose of this study is to determine the effectiveness of village fund management for community empowerment in improving welfare. This research used descriptive research method through a qualitative approach. The results shew that the management of Trutup village funds was in accordance with the plan, which was used as village development and village community empowerment. Village development carried out in the village of Trutup includes road repairs, street lighting, and construction of irrigation channels. The implementation of village community empowerment activities was used to provide assistance to support the activities of Social Institutions and the costs of building physical facilities and infrastructure that support village socio-economic improvement. The realization of village fund allocations was carried out through two stages, namely planning and implementing village fund management. Although there were some that have not been implemented, but some planning of village fund management that has been implemented has been able to improve the level of community welfare, such as PKK women who ran businesses as outputs of training activities which are one of the community empowerment activities in Trutup village. In addition, the construction of new roads can facilitate the access of the Trutup village community to carry out mobility in order to carry out economic activities and the construction of road infrastructure in the form of lighting along the Trutup village road which gives a sense of security to the road user community, especially the Trutup village community. The conclusion is management of Trutup village funds is effective in increasing the welfare of Trutup’s civil.Keywords : Village Fund, Community Empowerment, Community Welfare.